The Rate of Leaf Litter Decompositions and Nutrient Release Patterns of Four Selected Agroforestry Tree Species in Southern Ethiopia - Daba Misgana Bekele; Asmelash Tesfaye Gebremedhin (International Journal of Forestry Research)
The aim of this study was to examine the decomposition rates of leaf litter, nutrient release patterns, and the relationship between nutrient release from leaf litter and soil nutrients of four specific agroforestry tree species of Balanites aegyptiaca (L.) Delile, Terminalia brownii (Fresen.) J. Léonard, Croton macrostachyus Hochst, and Cordia africana Lam. The study was conducted in the Gamo zone of southern Ethiopia, specifically at three sites, i.e., Lante, Chano, and Shara. For this study, the litterbag techniques was employed, which involved placing dried leaf litter into nylon mesh bags. These nylon mesh bags were then buried in the soil and periodically retrieved to assess the remaining litter mass and its associated nutrients. SPSS version 24 software was used to analysis the collected data. Significant differences in half-life and turnover rates were observed among all tree species (P<0.05). Terminalia brownii exhibited the longest half-life of 21.7 days and the highest turnover rate of 93.9 days, while Balanites aegyptiaca had the shortest half-life and turnover rates at 14 days and 60.6 days, respectively. The release rates of organic carbon from leaf litter of Terminalia brownii, Croton macrostachyus, and Cordia africana showed negative correlations with soil organic carbon, whereas Balanites aegyptiaca displayed a significant positive correlation, with Pearson values of -0.94, -0.397, -0.95, and 0.71, respectively (P<0.05). Additionally, the rates of nutrient release varied among the four tree species across different time intervals. Generally, this research finding indicates that the rate of leaf litter decomposition and nutrient release patterns vary significantly among the four selected agroforestry tree species.